Possibilidades de desenvolvimento da atenção voluntária com crianças de 5 anos - Graciliano, Eliana Cláudia (2019)
The research question that guided this doctoral work was: What concepts and strategies are used in the routine of a classroom with 5 year old children during the development of these children's voluntary care? The general objective was to identify and analyze the processes of development or not of voluntary care, based on the concepts and strategies worked in the routine of a classroom with children of 5 years old. The methodology was subsidized by the Historical-Cultural Theory, based on the method of dialectical historical materialism. The instruments used were field diaries, official college documents, observation protocol, video camera and voice recorder. Regarding the research phases, there were four: introductory, field, analytical and conclusive. The first contemplated the submission and permission to conduct the research to the UFSCar Ethics Committee, the second consisted of preparatory observation and participant observation in the school class, the third in the study of the information produced with the children, choice of analysis criteria, systematization the guidelines for the analysis and selection of the didactic sequence based on the type of research, the qualitative and, finally, the last phase for the interpretation of information and analysis approaches. The unit of analysis was configured in the possibilities of developing voluntary care present in activities developed by the teacher of a 5-year-old child in the stage of Early Childhood Education. The results indicated that five strategies used by the teacher drew the attention of children in teaching situations, they were: guide questions; technology, practical actions, role play and written record added to the pictorial. Regarding the concepts worked on, we saw that the theme referred to the basic traffic laws associated with everyday concepts. When we relate these two elements [strategies and concepts] in the routine of a classroom with 5 year old children to the development processes of voluntary care, we identify that there was success in the way of provoking it. However, the pedagogical processes, in the way they were organized and proposed to children, presented limitations regarding the stability of concentration and the distribution of attention, fundamental characteristics for the development of voluntary care. The research evidenced, therefore, that the deepening of the quality of thought and language in human beings depends on the type of voluntary attention developed during the experiences in social relationships: the more intentionally mediated, the more it becomes qualified; the greater the awareness and volitiveness in voluntary care processes at school, the more chances of development and mastery of human conduct. So, it is possible to develop activities in Early Childhood Education that aim to develop the voluntary care of children aged 5 years